Medical students' perception and satisfaction on peer-assisted learning in formative OSCE and its effectiveness in improving clinical competencies - Latjatih, Nurul Haizum FarahDiyana (Emerald Publishing, 2022)
Purpose: Peer-assisted learning (PAL) in formative objective structured clinical examination (OSCE) is an approach used to evaluate the students' clinical competence. This study aims to determine the PAL effectiveness in the formative OSCE in improving clinical competencies and the students' perception and satisfaction of PAL. Design/methodology/approach: Sixty-seven Year 2 medical students experienced PAL in a formative OSCE setting. A self-administered questionnaire was distributed to evaluate their perception and satisfaction on PAL. The effectiveness of the sessions was determined by comparing their OSCE scores between the pre- and post-intervention. Findings: Forty-three students completed the intervention and had the experience to assess their peers as well as being assessed during formative OSCE. However, only 26 students managed to attend both pre- and post-intervention OSCE. It was found that there was a significant improvement of OSCE score after the PAL sessions. Over 97% of these students perceived positively and were satisfied with the sessions and thought that formative OSCE gave an opportunity to improve their learning and develop self-confidence in clinical skills. Originality/value: The findings suggested that PAL in the formative OSCE is a good opportunity to help in students' learning and improve their clinical competencies apart from learning with experts.